2021
DOI: 10.1371/journal.pone.0251514
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of Bacillus velezensis strains isolated from stingless bee products against methicillin-resistant Staphylococcus aureus

Abstract: Infections caused by methicillin-resistant Staphylococcus aureus (MRSA) have reached epidemic proportions globally. Therefore, there is an urgent need for a continuous supply of antibiotics to combat the problem. In this study, bacteria initially identified as species belonging to the Bacillus amyloliquefaciens operational group were re-identified based on the housekeeping gene, gyrB. Cell-free supernatants (CFS) from the strains were used for antimicrobial tests using the agar well diffusion assay against MRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…In the study by Nishio et al [ 41 ], the antibacterial activity of honey produced by stingless bees Scaptotrigona postica and Scaptotrigona bipunctata against methicillin-resistant Staphylococcus aureus (MRSA) and sensitive S. aureus strains was verified. A recent study demonstrated broad inhibiting activity against MRSA strains by the supernatant of Bacillus velezensis isolated from stingless bees [ 44 ]. However, contrary to our study, most authors also report relevant antimicrobial action on Sensitive S. aureus (RRR).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Nishio et al [ 41 ], the antibacterial activity of honey produced by stingless bees Scaptotrigona postica and Scaptotrigona bipunctata against methicillin-resistant Staphylococcus aureus (MRSA) and sensitive S. aureus strains was verified. A recent study demonstrated broad inhibiting activity against MRSA strains by the supernatant of Bacillus velezensis isolated from stingless bees [ 44 ]. However, contrary to our study, most authors also report relevant antimicrobial action on Sensitive S. aureus (RRR).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the antibacterial activity of AMPs can be enhanced by modifying the structural properties of natural peptides [ 36 38 ]. In a similar report, the crude antimicrobial extract of Bacillus velezensis strains isolated from stingless bee products showed bactericidal activity against methicillin-resistant Staphylococcus aureus and was stable at various temperatures (40–80°C) [ 39 ]. Furthermore, Plantaricin LD1 produced by Lactobacillus plantarum LD1 showed stability at high temperatures (100°C for 20 min and 121°C for 15 min under 15 psi) and inhibited bacteria such as Staphylococcus aureus , urogenic Escherichia coli , Pseudomonas aeruginosa , Salmonella typhi , Shigella flexneri and Vibrio sp [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The isolation procedure used the spread plate method of each serial dilution on International Streptomyces Project-2 (ISP-2) medium, with incubation at 30°C for 3 days under aerobic conditions. In another previous study, B. velezensis isolated from stingless bee products of Heterotrigona itama exhibited antimicrobial activity against methicillin-resistant Staphylococcus aureus ( 3 ). In this study, we present the annotated genome sequence of B. velezensis GMEKP1 and report the potential active compounds encoded by its biosynthetic gene clusters (BGCs).…”
Section: Announcementmentioning
confidence: 92%